ChemInform Abstract: β‐Cyclodextrin‐Mediated Acetic Acid Catalyzed Diastereoselective Mannich Reaction in Water. Issue 1 (3rd January 2013) - Sukumari, Subbiah; Azath, Ismail Abulkalam; Pitchumani, Kasi
Abstract The title reaction occurs in a syn‐selective fashion when propiophenone(III) is utilized as the ketone moiety, and in an anti selective manner when cyclohexanone (III) is utilized.